COMPARISON OF CALCIUM ACETATE WITH CALCIUM CARBONATE AS PHOSPHATE BINDER IN PATIENTS ON MAINTENANCE HAEMODIALYSIS - Saif, Imran; Halim, Abdul; Altaf, Ashfaq; Saif, Mohsin; Khalid, Muhammad; Ahmad, Dilshad; Imran, Humera (Journal of Ayub Medical College Abbottabad, 2007)
Background: Hyperphosphatemia is common in end-stage renal disease patients. Objective of this study is to compare the hypercalcaemic effect and phosphate binding power of calcium acetate and calcium carbonate in end-stage renal disease patients on maintenance haemodialysis. Methods: This randomised control trial was conducted in four phases with calcium acetate or calcium carbonate. Sixty-four patients on haemodialysis were randomly divided into 2 groups. After a washout period of 2 weeks, each group was given calcium acetate or calcium carbonate for 2 months. After another washout period the patients were crossed over and again received these drugs for 2 months. Serum Calcium, phosphate, and albumin were analysed on Selectra E auto analyser at completion of each phase of study. Hypercalcaemic effect was defined as serum calcium >2.54 mmol/l, and phosphate binding power as serum phosphate <1.61 mmol/l. Results: Forty-one patients completed the study. Though lower dose of calcium acetate was used, it resulted in equally good control of hyperphosphatemia as compared with calcium carbonate therapy [1.37 mmol/l (SD 0.33) vs. 1.46 mmol/l (SD 0.34), p=0.16]. Incidence of hypercalcaemia was higher with calcium carbonate therapy (2.73ï‚±0.67 mmol/l vs. 2.32ï‚±0.28 mmol/l, p<0.01). Both drugs were well tolerated, but patients more frequently complained of muscle cramps while taking calcium acetate. Conclusions: It is concluded that calcium acetate has similar effect on serum phosphate levels as compared to calcium carbonate in patients on maintenance haemodialysis. However, calcium acetate results in lesser frequency of hypercalcaemia as compared to calcium carbonate. Tolerance to both drugs was similar, though patients complained of more muscle cramps while taking calcium acetate. KEY WORDS: Calcium acetate, Calcium carbonate, Hyperphosphatemia